"Unileiros" na cidade:: memórias e preconceitos em Foz do Iguaçu - PR (2010-2017) (Revista de História Regional, 2022)
ABSTRACT: This text aims to understand the memories of students from the Federal of Latin American Integration – UNILA, in the city of Foz do Iguaçu – PR, having as a cut the period of its creation, 2010, until 2017. For that, we will use as sources interviews with young UNILA students of different nationalities, produced between 2013 and 2017. Interviews of ten students are mobilized - two Brazilians and eight foreigners – and analyzed from theoretical and methodological contributions of Oral History. The memories of these students experiences were marked by transformations in their relations with the city. They narrated a first moment when they would have been well received by the city, followed by a process, from 2012, of construction and perception of prejudices and stereotypes made about themselves in that city. Throughout the text we analyze this process, trying to understand this movement, as well as tactics produced by students in their dialogues with city spaces. Through our analyses, it was possible to perceive student memories crossed and resignified by tensions, prejudices and tactics tried and built in the city.